Demand and Supply of Organic Food - The Indian Perspective - Ghosh, Sharmita; Havaldar, Deepak (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
In order to understand the state of the organic market, it is not sufficient to take into account only the demand aspect where role of wholesalers and consumers 'with respect to purchase of organic products is analyzed. Neither will the analysis of the organic market be complete if only supply of organic products with farmers playing a major role is considered. Both demand and supply factors need to be considered together. Today, consumers are somewhat aware of the positive effects of organic farming, yet, demand is not increasing much. Some of the reasons being- consumers think that organic products are expensive, they don’t have easy access to organic products, also they feel that products may be sold as Organic even when they are not. To understand the situation on the supply side, it must be understood that it takes three years for farmers to switch over from Green Revolution agriculture to organic agriculture. Initially for two to three years, there will be less yield as the soil takes time to regain its fertility with the use of organic inputs. Only if there is Governmental support in the form of subsidized organic inputs, provision of trainings imparting knowledge for best practices, will there be motivation to switch over to organic farming. However, for farmers already practicing organic farming, yield may be almost same or even higher if best practices are followed. Moreover, on the supply side, there are marketing issues related to selling of organic products at a premium price. The cost of processing and storage of organic products is high and a lot of cautiousness in handling such products also has to be exercised. This paper will look at the challenges on both the demand and supply sides in respect of the organic market.